IDENTIFIKASI POTENSI EKOWISATA DI KAWASAN BERNILAI KONSERVASI TINGGI SITUS BUDAYA MAKAM KERAMAT EYANG DALEM CAGEUR - Yesi Elia Widiawati; Iing Nasihin; Nina Herlina (Faculty of Forestry and Environment, Universitas Kuningan, 2022)
The Cultural Site of Makam Eyang Dalem Cageur is a High Conservation Value Area which has a function as a local traditional cultural identity. This study aims to determine the potential of ecotourism in The Cultural Site of Makam Eyang Dalem Cageur. The primary data in this study is data related to ecotourism potential which includes attractions (types of flora, fauna, natural landscapes and socio-cultural). data collection in this study used flora (area species curves), fauna (transect lines), landscapes (observation), accessibility (observation, accommodation (interview) and infrastructure (observation). The data obtained were analyzed by qualitative descriptive to determine the potential for attractiveness, accessibility, accommodation and infrastructure. The results showed that there were 16 species of flora potential, 12 species of fauna, canopy which is a meeting place and as a life support and a source of water for the people of Darma District, social and cultural culture which has a pagelaran babarit, pilgrimage to Eyang Dalem Cageur, air kejayaan and 7 cultural values which include: cultural values of security, order, cleanliness, coolness, beauty, hospitality and memories, accessibility is very good because it is on the brass earring route and is a routes that are often passed, accommodation is good because the manager provides homestays for visitors and good infrastructure to support the cleanliness of the Eyang Daleum Cagur Cemetery Cultural Site.Situs Budaya Makam Eyang Dalem Cageur merupakan Kawasan Bernilai Konsevasi Tinggi yang memiliki fungsi sebagai identitas budaya tradisional lokal. Penelitian ini bertujuan untuk mengetahui potensi ekowisata di Kawasan Bernilai Konservasi Tinggi Situs Budaya Makam Eyang Dalem Cageur. Data primer dalam penelitian ini data terkait potensi ekowisata yang mencakup daya tarik (jenis flora, fauna, bentang alam dan sosial budaya.pengumpulan data dalam penelitian ini menggunakan flora (kurva spesies area), fauna (garis transek), bentang alam (observasi),aksesibilitas (observasi, akomodasi (wawancara) dan sarana prasarana (observasi). Data yang diperoleh dianalisis dengan deskriptif kualitatif untuk mengetahui potensi daya tarik,aksesibilitas, akomodasi dan sarana prasarana. Hasil penelitian menunjukkan bahwa potensi flora terdapat 16 jenis, fauna terdapat 12 jenis, Tajuk yang rapat dan sebagai penyangga kehidupan dan sumber mata air untuk masyarakat Kecamatan Darma, sosial budaya yang memiliki budaya pagelaran babarit, ziarah makam eyang dalem cageur, air kejayaan dan 7 nilai kebudayaan yang meliputi: nilai budaya keamanan, ketertiban, kebersihan, kesejukan, keindahan, keramahan dan kenangan, aksesibilitas sangat baik karena berada di jalur subang kuningan dan merupakan jalur yang sering dilewati,Akomodasi baik dikarenakan pengelola menyediakan homestay untuk pengunjung dan Sarana Prasarana yang baik dalam menunjang kebersihan Situs Budaya Makam Eyang Dalem Cageur